Polar pesticide analyses validation of glyphosate determination in soil by LC-MS/MS - Gorica Vuković (Proceedings of the International Symposium on Analytical and Environmental Problems, 2016)
Although glyphosate is a heavily applied herbicide worldwide, the risk of environmental contamination through transport mechanisms of this substance is still not well documented and the methods for its analysis are usually very complex and nor sensitive enough. In the measurement procedure with LC-MS/MS, a negative mode was used. FMOC-Cl derivatized glyphosate ions were identified by the precise determination of their ion mass. The LOQ was 0.01 mg/kg, with recovery of 101.4±4.49% and linearity over 0.99. The obtain method demonstrates the sensitivity, which enables measurements of glyphosate soil as a matrix. The success of the new extraction method was confirmed by measuring spiked soil samples to control recovery, linearity, LOD and LOQ.